(untitled) (Journal of Contemporary Philology, 2023)
This text considers the problem of Self in literature through analysis of the position of the "narrative I" in Marcel Proust’s novel In Search of Lost Time. This novel unites the fictional with the autobiographical discourse and directly addresses the problem of the fictional representation of the Self. This article thus examines the aesthetics of simultaneity and supplementing, which in the case of Proust represents the initial and the final point of the artwork. Through simultaneity in the narration, Proust creates a rather specific relationship with temporality, which in turn, dismisses time as a constant present, but also initiates a collision of the positions of the "narrative I", and by that, propels a dissemination of identity. These narrative strategies of Proust provide a systematic abolition of the borders between the fictional and the autobiographical discourse. Thus, with Proust, autobiography gains the status of interpreter, which affords an interpretative recovery of life (the documentary) within the novel (the fictional). One of the key objectives of this article is to emphasize the transformation of this interpretative tendency in terms of time and selfhood in an aesthetic act. These complex and multilayered relations in the novel In Search of Lost Time reveal that Proust’s "journey into the depths of selfhood” in fact represents an evocation of a certain loss of selfhood and of temporality which is neither given nor regained, but in which time is continuously lost or forgotten.